Broadcast Algorithm utilizing Co-operative communication for minimizing Energy consumption in Two Tiered Wireless Sensor Network - Mehmood, Usman (The Graduate School, Ajou University, 2013)
An energy efficient broadcast algorithm has been proposed that takes the advantage of co-operative communication for Two-tiered Wireless Sensor Networks (TT-WSN). Co-operative communication allows the nodes in the network to cooperate with each other by sharing their antennas and thus making a Virtual MIMO (Multiple input multiple output) system. By enabling the co-operative communication within the nodes, we can provide major and considerable energy savings for the broadcast process in TT-WSN. In two tiered Wireless Sensor network (TT-WSN) we divide the network in two tiers. In Lower tier there are sensor nodes which are capable of sensing the data around the surroundings and forward it to the one hop neighbor relay node. The Upper tier consists of the more powerful Relay nodes. The responsibility of the Relay nodes is to deliver the data to the Base stations through multiple connected relay nodes. In the proposed algorithm we select a smaller portion of Relay Nodes as Forwarding Nodes to forward the broadcast message exploiting co-operative communication. Simulation and performance analysis have shown that the energy consumption is less with the proposed scheme and it has also reduced the redundant transmission of the same message.
학위논문(석사)아주대학교 일반대학원 :컴퓨터공학과,2013. 2